Applied Theatre Facilitates Dialogue about Career Challenges for Scientists - Verónica A. Segarra (American Society for Microbiology, 2017)
The design of programs in support of a strong, diverse, and inclusive scientific workforce and academe requires numerous difficult conversations about sensitive topics such as the challenges scientists can face in their professional development. Theatre can be an interactive and effective way to foster discussion around such subjects. This article examines the implementation and benefits of such interactive strategies in different contexts, including the benefits of getting early career academics and professionals talking about some of the situations that women and underrepresented minorities face in the workplace, while allowing more seasoned professionals and colleagues to join in the conversation.